2011
DOI: 10.1590/s1516-80342011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da saúde vocal de cantores amadores de igreja evangélica

Abstract: OBJETIVO: Investigar o perfil de saúde vocal de cantores amadores de louvores evangélicos com relação a queixas, hábitos e dificuldades vocais vivenciados durante a prática do canto em indivíduos dos gêneros masculino e feminino. MÉTODOS: Participaram 55 sujeitos, com idade entre 18 e 50 anos, os quais responderam a um questionário auto-aplicável sobre identificação de hábitos vocais e possíveis queixas de voz falada e cantada. RESULTADOS: Os cantores religiosos evangélicos amadores relataram queixas relaciona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
0
15
0
5
Order By: Relevance
“…Gospel singers generally develop their singing for personal satisfaction, vocation or talent, becoming in this manner amateur singers, almost always without training or specialized coaching (3) . Amateur singers can present diverse complaints in relation to their voice and in terms of vocal tract discomfort symptoms, such as: hoarseness, failures and loss of voice, difficulty to attain high or low notes, constant coughing, pain in the neck region, as well as a tight sensation or lump in their throat and a feeling of dryness (4,5) . These alterations can be a consequence of a lack of understanding of vocal anatomy and physiology, the inappropriate use of the voice, and a lack of knowledge of specific vocal techniques and training for use with the singing voice, which can also compromise the voice-related quality of life of the singer.…”
Section: Introductionmentioning
confidence: 99%
“…Gospel singers generally develop their singing for personal satisfaction, vocation or talent, becoming in this manner amateur singers, almost always without training or specialized coaching (3) . Amateur singers can present diverse complaints in relation to their voice and in terms of vocal tract discomfort symptoms, such as: hoarseness, failures and loss of voice, difficulty to attain high or low notes, constant coughing, pain in the neck region, as well as a tight sensation or lump in their throat and a feeling of dryness (4,5) . These alterations can be a consequence of a lack of understanding of vocal anatomy and physiology, the inappropriate use of the voice, and a lack of knowledge of specific vocal techniques and training for use with the singing voice, which can also compromise the voice-related quality of life of the singer.…”
Section: Introductionmentioning
confidence: 99%
“…The dry throat may be related mainly to insufficient hydration. The present study allows to observe that the gospel singers reported complaints are common in this population 10,11 . These data reinforce the importance of proper voice prepare and speech-language following regarding voice care guidance, hydration, and voice exercises practice that may be used before and after singing as warm up and cooling down in order to ease these complaints 9,10,17,27 .…”
Section: Resultsmentioning
confidence: 59%
“…These data reinforce the importance of proper voice prepare and speech-language following regarding voice care guidance, hydration, and voice exercises practice that may be used before and after singing as warm up and cooling down in order to ease these complaints 9,10,17,27 . Besides, the lack of information about vocal health may contribute to developing laryngeal disturbances and dysphonia through time 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations